The Feasibility of Using Dredged Bottom Sediments as an Agricultural Soil - Mudroch, Alena (My University, 1974)
The utilization of contaminated bottom sediments as agricultural soil was investigated as a new approach of the dredged sediment disposal.
Bottom sediments collected from Hamilton Harbour~ Humber Bay Port Stanley~ Detroit River Mouth~ and Lake St. Clair were used for the determination of chemical, physical and biological properties considered important for the evaluation of bottom sediments as agricultural soil.
It was proved in leaching experiments and lysimeters that the concentrations of elements, released from the bottom sediments dispersed in water ~ were Imver than those recommended for water for public use with the exception of manganese and nickel. (Cd < 0.001 mg/I, Cr < 0.2 mg/l, Cu 0.08 mg/l, Fe 0.08 mg/l, pb < 0.001 mg/I, Mn 2.9 mg/l, Hg < 0.05 mg/l, Ni 0.07 mg/l, Zn 1.1 mg/l). The suitability of contaminated bottom sediments from Hamilton Harbour, Humber Bay and Detroit River as agricultural soil was verified in greenhouse experiment by -planting tomatoes and corn with a good crop yield. The crop yield of the Humber Bay tomato plants was best, follmved by those of Hamilton Harbour and Detroit River.
Tomato plants and corn did not take up various elements in the proportions in which the elements occurred in the sediments, but exerted a selective action, absorbing greater amounts of some elements than others. Tomato plants took up nutrients and trace elements only to a certain limiting concentration characteristic for individual plant organs. The concentrations were comparable with those found by soil scientists studying the uptake of elements from soils.
Following maximum concentrations were determined for tomato fruit grown in Humber Bay sediment: K 37,000 mg/kg, Mg 2,100 mg/kg, Ca 1,750 mg/kg, Zn 40 mg/kg, Sr 30 mg/kg, Cu 23 mg/kg, Pb 12 mg/kg, Co 7 mg/kg, Cd 2 mg/kg - Arsenic, molybdenum, manganese, chromium, nlckel and mercury were below the levels of detection.
Keywords: Geology; Geology